Ti‐Substituted NaNi0.5Mn0.5‐xTixO2 Cathodes with Reversible O3−P3 Phase Transition for High‐Performance Sodium‐Ion Batteries. Issue 19 (15th March 2017) - Wang, Peng‐Fei; Yao, Hu‐Rong; Liu, Xin‐Yu; Zhang, Jie‐Nan; Gu, Lin; Yu, Xi‐Qian; Yin, Ya‐Xia; Guo, Yu‐Guo
Abstract : Sodium‐ion batteries (SIBs) have been considered as potential candidates for stationary energy storage because of the low cost and wide availability of Na sources. O3‐type layered oxides have been considered as one of the most promising cathodes for SIBs. However, they commonly show inevitable complicated phase transitions and sluggish kinetics, incurring rapid capacity decline and poor rate capability. Here, a series of sodium‐sufficient O3‐type NaNi0.5 Mn0.5‐ x Ti x O2 (0 ≤ x ≤ 0.5) cathodes for SIBs is reported and the mechanisms behind their excellent electrochemical performance are studied in comparison to those of their respective end‐members. The combined analysis of in situ X‐ray diffraction, ex situ X‐ray absorption spectroscopy, and scanning transmission electron microscopy for NaNi0.5 Mn0.2 Ti0.3 O2 reveals that the O3‐type phase transforms reversibly into a P3‐type phase upon Na+ deintercalation/intercalation. The substitution of Ti for Mn enlarges interslab distance and could restrain the unfavorable and irreversible multiphase transformation in the high voltage regions that is usually observed in O3‐type NaNi0.5 Mn0.5 O2, resulting in improved Na cell performance. This integration of macroscale and atomicscale engineering strategy might open up the modulation of the chemical and physical properties in layered oxides and grasp new insight into the optimal design of high‐performance cathode materials for SIBs. Abstract : Here, a structure optimization of NaNi0.5 Mn0.5 O2 through a partial Ti substitution strategy is designed, yielding a series of sodium‐sufficient O3‐NaNi0.5 Mn0.5‐ x Ti x O2 (0 ≤ x ≤ 0.5) cathodes for sodium‐ion batteries for the first time. The substitution of Ti for Mn could suppress irreversible multiphase transformation in the high voltage regions that is usually observed in O3‐type NaNi0.5 Mn0.5 O2 and retain a highly reversible O3−P3 phase transition, resulting in improved Na cell performance.